A Comparative Study of the Concepts of Torah in the Hebrew Bible and Li in Zuozhuan. Issue 3 (18th June 2019) - Jiang, Zhenshuai
Abstract: The ancient Israelite concept of Torah as law developed from its initial reference to legal stipulations into a system representing almost everything of social‐political and cosmic significance in the postexilic period. Likewise, the ancient Chinese notion of li (禮) transformed from reference to specific rituals into an abstract, all‐inclusive, collective concept of cosmic dimensions. This study compares the notions of Torah in the Hebrew Bible (particularly in the Psalms) and li in Zuozhuan (particularly in "Lord Zhao 25"). These concepts share similarities but also differ. They provide mutual insights from perspectives of kingship, the public, and natural order.